The genre of the fiqra in the works of Askad Mukhtor and Erkin Azam - Raykhona, Khojaeva (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This thesis analyzes the features characteristic of the fiqra genre and their examples. In particular, the specific features, subject-content and relevance of the fiqra belonging to the works of Askad Mukhtor and Erkin Azam are highlighted.